Sifat Kimia dan Organoleptik Permen Jelly Buah Naga (Hylocereus Polyrhizus) dengan Penambahan Karagenan sebagai Gelling Agent - hamka nurkaya (Jurusan Teknologi Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2020)
ABSTRACT Dragon fruit is an Indonesian agricultural commodity that contains many essential nutrients for the body. Dragon fruit is known to reduce cholesterol and balance blood sugar levels in the body. Unfortunately, dragon fruit is easily damaged. In addition, dragon fruit also often experiences price declines especially when the amount of harvest is abundant. Therefore, efforts are needed to process dragon fruit into processed products of high economic value; one example is to process them into jelly candies. In this research, jelly candies were made from dragon fruit by using carrageenan as a gelling agent. This study aims to determine the chemical properties and the level of preference of panelists on dragon fruit jelly candy with the addition of carrageenan at different concentrations. The experimental design used in this study is a completely randomized design with 1 treatment factor, namely the difference in carrageenan concentration (3%, 5%, and 7%). The results showed that the water content of dragon fruit jelly candy at all levels of carrageenan concentration had fulfilled SNI-3547-2-2008 with an average value ranging from 4.78 to 6.61% (maximum water content according to SNI was 20%). And the ash content required by SNI-3547-2-2008 for jelly candy is 3% according to the treatment of adding 3% carrageenan with a value of 2.91%. The organoleptic test showed that the best treatment that panelists prefer is the treatment with the addition of 3% carrageenan with an average value of aroma 3.33 (somewhat like), color 3.60 (like), taste 3.53 (like) and texture 3.45 (somewhat like).